Determination of estrus in Aceh cows based on the van Eerdenburg method - Qathrinnada Ramadhana; Ginta Riady; Hafizuddin Hafizuddin; Cut Nila Thasmi; Erdiansyah Rahmi; Amalia Sutriana (Universitas Airlangga, 2022)
Accurate determination of estrus status in an animal based on an appropriate estrus detection method can guarantee the cows' pregnancy after mating. This study aims to determine the estrus status of Aceh cows using the van Eerdenburg estrus behavior scoring method. This study was conducted from 22 January to 12 February 2021, at the Technical Implementation Unit for Animals of the Faculty of Veterinary Medicine, Universitas Syiah Kuala, Banda Aceh, Indonesia. The sample used was eleven Aceh cows aged 4-6 years old. Parameters observed were the number of cows exhibiting signs of estrus using the estrus behavior scoring method. The accuracy of estrus detection was confirmed by palpation per rectum to detect the presence of uterine tone. By observing signs of estrus using the method studied, 90.9% (10/11) of the cows were determined to be in estrus. Confirmation by the presence of uterine tone showed a 100% accuracy rate. The most effective sign of estrus was the passivity of the cow when being ridden by another cow or bull. This study concluded that estrus status in local cows could be determined using the estrus behavior scoring of the van Eerdenburg method.